POLA ASUH AKTIVITAS FISIK TERHADAP RISIKO KEJADIAN GIZI LEBIH PADA ANAK PRASEKOLAH DI KECAMATAN NGESREP DAN TEMBALANG, SEMARANG - Rahmah, Nadya Diena; Ardiaria, Martha; Dieny, Fillah Fithra (GIZI INDONESIA, 2019)
The preschool period is identified as a critical period for the development of childhood overweight. Physical activity and food intake are factors that affect nutritional status. Physical activity of preschool children is affected by parents through physical activity parenting. The objective of this study was to analyze the impact of physical activity parenting practice among overweight preschool children. This research was a case-control study with preschool children as the subjects. The total subject was 40 and divided into case and control groups. Case group were selected based on z-score and matched with sex in control group. Nutritional status was measured based on weight-for-height z-score (WHZ). Physical activity level was measured using the Preschool-Age Physical Activity Questionnaire (Pre-PAQ). Physical activity parenting practice was identified using the Preschooler Physical Activity Parenting Practice Questionnaire (PPAPP-Q). Food intake history was obtained using Semi Quantitative Food Frequency Questionnaire (SQFFQ). Data were analyzed using Chi-square, Fisher's Exact, and Logistic Regression. Result showed that physical activity parenting practice (p=0,011) and physical activity (p=0,004) were risk factor of overweight among preschool children. Children with inactive physical activity were 7.66 times more likely to become overweight. Children with parents applied parenting practices discourage toward physical activity were 6.16 times more likely to become overweight. Children need to always be active at least 120 minutes a day. Parents recommend to apply physical activity parenting to encourage them to be more active physically.